ANALISI BREAK EVEN POINT (BEP) UNTUK MELIHAT STRATEGI KEBERLANJUTAN USAHA MEBEL KAYU DI KABUPATEN TAKALAR PERIODE 2021-2025 (STUDI KASUS : UD.ISRA MEUBLE) - Ika Nurinsana Zahra; Muchriana Muchran; Amelia Rezki Septiani Amin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study analyzes the Break Even Point (BEP) to assess the sustainability strategy of a wooden furniture business at UD. Isra Meuble in Takalar Regency for the period 2021–2025. Using a quantitative descriptive approach based on financial report data including fixed costs, variable costs, and sales over five years, the results indicate that fixed costs increased from Rp379,000,000 in 2021 to Rp486,000,000 in 2025, while variable costs fluctuated from Rp475,400,000 to Rp621,100,000. Despite rising costs, actual sales consistently exceeded the break-even point each year. In 2021, sales of Rp813,000,000 surpassed the BEP of Rp673,354,458, producing a margin of safety of 17.18%. The best performance was recorded in 2023 with a margin of safety of 46.08% and net profit of Rp295,230,000. The most critical period was 2024 with a margin of safety of only 8.42% due to a 56.25% increase in fixed labor costs. By 2025, the business recovered with a margin of safety of 26.91%. BEP analysis provides a basis for setting sales targets, controlling costs, and formulating sustainability strategies through material efficiency, energy optimization, waste utilization, workforce development, and digital green marketing via SIPLah